2011
DOI: 10.1111/j.1365-2915.2011.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Beetles and flies collected on pig carrion in an experimental setting in Thuringia and their forensic implications

Abstract: Decomposition processes and insect succession were analysed on a total of eight pig (Sus scrofa) carcasses. The survey was carried out in four different periods between November 2007 and August 2008 and on two different substrates (meadow, concrete floor close to a building). The experiments were placed in a rural site in the surroundings of Jena, Thuringia. The duration and specificity of the different decomposition stages were dependent on season, weather and quality and quantity of insect colonization. Wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…It must be mentioned that Hennig (1943) described the morphology of the CPS and anterior spiracles of S. nigriceps (named as Piophila foveolata Meigen) larvae from the characters observed on a puparium of this species, highlighting that the number of rows of spines on the ventral creeping welts could not be confirmed from such a specimen. The first author of the current manuscript has studied some larvae of S. nigriceps collected in a carrion-succession study (see Anton et al 2011) which showed two rows of spines on the ventral creeping welts. The presence of two rows of spines on the ventral creeping welts is therefore a common character of both L. varipes and S. nigriceps, but it is also shown by the larva of Lasiopiophila pilosa (Staeger), which conversely show anterior spiracles with lobes arranged in a single group (McAlpine 1977).…”
Section: Validity Of the Genus Liopiophila And Systematics Of Piophilmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be mentioned that Hennig (1943) described the morphology of the CPS and anterior spiracles of S. nigriceps (named as Piophila foveolata Meigen) larvae from the characters observed on a puparium of this species, highlighting that the number of rows of spines on the ventral creeping welts could not be confirmed from such a specimen. The first author of the current manuscript has studied some larvae of S. nigriceps collected in a carrion-succession study (see Anton et al 2011) which showed two rows of spines on the ventral creeping welts. The presence of two rows of spines on the ventral creeping welts is therefore a common character of both L. varipes and S. nigriceps, but it is also shown by the larva of Lasiopiophila pilosa (Staeger), which conversely show anterior spiracles with lobes arranged in a single group (McAlpine 1977).…”
Section: Validity Of the Genus Liopiophila And Systematics Of Piophilmentioning
confidence: 99%
“…Anton et al 2011;MartĂ­n-Vega and Baz 2013). Despite L. varipes appears to be of smaller economic and hygienic importance than other piophilid species, it may be common on food industry premises (Zuska and LaĆĄtovka 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of previous pig carcass studies [26, 38–40] and case histories [41–44], a list of definitive insect species was prepared for the rural habitats of Central Europe (Online Resource: ESM 2). The only precondition the species had to meet was regular breeding in large cadavers.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the next step in the development of the method was designed for five species of the genus Sarcophaga from five different subgenera. Sarcophaga albiceps , S. argyrostoma , S. caerulescens , S. melanura , and S. similis were previously found to be frequent visitors and successful colonizers of large animal carrion and human corpses [44,45,46,47,48,49,50]. As for the six Lucilia species, a genus pattern could be generated from these five Sarcophaga species (Figure 6) and species-specific pattern variations were found [51].…”
Section: Approach From the Biological Perspectivementioning
confidence: 96%